Are season of birth, climate, and parental age predictors of adult temperament, character, anhedonia, suicidality, and self-harm? - Fountoulakis, Konstantinos N.; Fountoulakis, Nikolaos K. (Frontiers in Psychiatry, 2025)
IntroductionThe aim of the current study was to investigate the relationship of temperament and suicidality with the season of birth, climate variables, and parental age.Material and methodsThe study sample included 701 subjects (aged 18–67 years; 59.48% females). The protocol gathered the precise date of birth, parental age at delivery, temperament and personality data (TEMPS-A, NEO-PI-3, TCI, and CAMT), and suicidality data (RASS). Epidemiological data concerning suicides and climate data were also obtained.ResultsNone of the ‘classic’ temperament and personality variables of the three major models (TEMPS, TCI, and NEO-PI) manifest any relationship with season of birth, climatic variables at birth, or parental age. Only the Internalized Interpersonal Emotion (IIE) from the CAMT manifested high scores for those born during spring and low scores for those born in summer and autumn. There was a weak but significant correlation between weight and BMI with all climate variables. Deaths by suicide manifested higher rates during the spring. Zodiacs were not related to any temperament or character facet.DiscussionOverall, our results point to the importance of the interplay between environmental and biological determinants of temperament and suggest that spring is related to deficits in affective interpersonal relating for those born during spring, and also to higher deaths by suicide in adults again during the same season. This could mean that this period of the year exerts an adverse effect on mental health, at least on vulnerable populations. Future research should focus on neurobiological differences in relation to the season of birth and climate, especially in the face of the changes in mental health that climate change might cause.